Blood‐brain barrier dysfunction and perioperative neurocognitive disorders: Cognitive Recovery after Elective Surgery (CREATES) study design and methods: Biomarkers (non‐neuroimaging) / Novel biomarkers. (7th December 2020) - Daiello, Lori A; Wang, Danny JJ; Jones, Richard N; Boxerman, Jerrold; Tremont, Geoffrey; O'Bryant, Sid; Kendall, Mark; Cioffi, William G; De Oliveira, Gildasio S.; Ott, Brian R; Inouye, Sharon K
Abstract: Background: Impaired blood‐brain barrier (BBB) function is observed in preclinical models of postoperative cognitive dysfunction and has been identified as an early indicator of neurodegeneration in those at risk for Alzheimer's disease. Using a novel brain imaging technique, water exchange index mapping MRI (WEI‐MRI), the CREATES study will investigate the extent to which BBB dysfunction predicts the incidence of perioperative neurocognitive disorders (postoperative delirium and postoperative cognitive dysfunction). Method: CREATES is an 18‐month cohort study that will enroll older adults without dementia (N=230) scheduled for major elective non‐cardiac surgeries under general anesthesia. The preoperative baseline evaluation includes WEI‐MRI brain imaging, neuropsychological tests, and blood sample collection for analysis of selected biomarkers associated with inflammation and microvascular dysfunction (soluble vascular adhesion molecule 1, soluble intercellular adhesion molecule 1, thrombopoietin, interleukin‐18, fatty acid binding protein, pancreatic polypeptide Y, chemokine I309, serum amyloid A, C‐reactive protein, alpha‐2‐macroglobulin, beta‐2 microglobulin, factor VII, adiponectin, apolipoprotein J, and neurofilament light). Delirium will be assessed daily during hospitalization using the Confusion Assessment Method diagnostic algorithm. Baseline assessments, including WEI‐MRI brain imaging will be repeated at postoperative month 3. Subsequently, neuropsychological testing and blood sample collection will be performed during follow‐up (months 6, 12, & 18). Incidence of mild cognitive impairment and Alzheimer's disease will be evaluated by an expert panel using NIA‐AA diagnostic criteria at postoperative months 12 and 18. Result: Primary analyses will investigate associations between 1) preoperative BBB permeability and incident postoperative delirium; and 2) postoperative BBB permeability and incident postoperative cognitive dysfunction during follow‐up. Relationships between serum biomarkers, BBB permeability, and incidence of neurocognitive disorders will be modeled in exploratory analyses. Conclusion: BBB dysfunction is an indicator of brain vulnerability and neurodegeneration that may also be an important risk factor for postoperative delirium and delayed or incomplete cognitive recovery. CREATES is the first study of perioperative cognitive outcomes to utilize WEI‐MRI brain imaging, an innovative technique to evaluate BBB integrity which does not require administration of intravenous gadolinium‐based contrast agent. The results will provide important insights into the underlying mechanism(s) of perioperative neurocognitive disorders and potential biomarkers of prognostic significance.